2012
DOI: 10.1118/1.4768161
|View full text |Cite
|
Sign up to set email alerts
|

A statistical approach to IMRT patient‐specific QA

Abstract: The authors have studied the analysis of variance on ion chamber measurements made for IMRT treatment plans on different sites, identified similarities and differences between different sites, and thereby evaluated the need for site-specific tolerances for QA acceptance policy. The authors have proposed a way to calculate the appropriate tolerances for different treatment sites and illustrated the clinical usage. Variability at each step of the process increases the uncertainty in the process. The authors have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 14 publications
0
18
0
Order By: Relevance
“…In addition to the anatomic parameters discussed herein, other parameterizations, such as portions of OAR outside the primary target fields and tumor site, can be easily considered. 6,11 Beam information, such as beam angles and field arrangements, can also be included. However, given that there are many such planning parameters, external factors, and anatomic parametrizations that could be included in this framework, an exhaustive model considering all risk factors is outside of the scope of this proof of concept.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the anatomic parameters discussed herein, other parameterizations, such as portions of OAR outside the primary target fields and tumor site, can be easily considered. 6,11 Beam information, such as beam angles and field arrangements, can also be included. However, given that there are many such planning parameters, external factors, and anatomic parametrizations that could be included in this framework, an exhaustive model considering all risk factors is outside of the scope of this proof of concept.…”
Section: Discussionmentioning
confidence: 99%
“…Individual, moving-range, standard deviation (SD), and exponentially weighted moving average (EWMA) charts were used to detect unusual trends in dose deviations between the TPS and delivered dose. 5,6 Alternatively, Nordström et al 7 found control charts to be effective for the continuous verification of monitor units and derived control limits that agree with international guidelines. However, the use of control charts for treatment plan evaluation has been limited due to planning process variability for each patient, including patient-and treatment-specific risk factors.…”
Section: Introductionmentioning
confidence: 97%
“…5 Additionally, using a 90% passing rate threshold to decide whether a plan is acceptable has also been identified as a significant limitation to detecting clinically relevant errors, and the development of site specific thresholds has been suggested. 11 The 90% threshold for all plans with composite analysis and global normalization was derived in Task Group 119, assuming that gamma failing rates followed a Gaussian distribution and determining what threshold will include 95% of plans passing QA. 12 With today's level of accuracy, however, this threshold is easily met by most plans if proper commissioning has been performed.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the tolerance limit can be established from the trend of the patient-specific QA result in each institution. However, few reports have been published about applying statistical methods to patient-specific QA [1012]. For example, no recommendations about the management method for patient-specific QA exist, though Pulliam et al .…”
Section: Introductionmentioning
confidence: 99%